Application of Whisker-Toughened Aerogel to Recycling of Used Polyurethane Sheets - Xiaohua Gu; Jiatong Chen; Shangwen Zhu; Qinglong Zhao; Yanxun Zhang; Qingyong Su (Gels)
In this study, a new environmentally friendly and efficient method for recycling and reusing waste polyurethane sheets is proposed. SiO2 aerogel was prepared using the sol–gel method, and mullite whiskers were introduced to enhance its toughness. The whisker-toughened aerogel was used in the degradation of waste polyurethane to produce modified recycled polyol, which was subsequently used to prepare recycled polyurethane foam insulation material. Following a series of tests, including Fourier-transform infrared spectroscopy, apparent density, viscosity, heat loss, and thermal conductivity, the results showed that when the aerogel with wt% = 0.9% mullite whiskers and 0.06 g of whisker-toughened aerogel were added, the viscosity was close to that of polyether polyol 4110. The optimal compressive strength of the resulting composite blister structure reached 817.93 MPa, with a thermal conductivity of 0.0228 W·(m·K)−1, demonstrating good thermal stability. These results indicate that the whisker-toughened aerogel effectively reduces the viscosity of the degraded materials and significantly improves the mechanical properties and thermal stability of the regenerated polyurethane thermal insulation materials. This research provides new ideas and new methods for waste polyurethane recycling and offers a new perspective for the research and development of thermal insulation materials.